Function versus appearance: the interaction between customer, stylist and engineer in vehicle design. (5th August 2014) - Maioli, M.
Car manufacturers are living in a changing world. Advanced technologies like informatics and robotics are altering the ways different company functions relate to product engineering, production and marketing. The stages in which new products are organised and programmed should be seen as survival conditions. They constitute the premise for revolutionised production based partly on our ability to foresee the product quality and performance required to satisfy user expectations, and partly on the use of the latest technologies in our organisation of production lines. The company structures involved in product development, research and design are required to provide continuous support for top level company decisions, never forgetting the real current or future demands of the market. The development of Fiat Auto's new 'Uno' is an example of how the use of an original methodology to compute significant design variables (aerodynamics/roominess/comfort/weight) can create a distinctive product.